Implementing Story Mapping In Facilitating Secondary School Students In Reading Narrative Text: An Action Research - Melissa Suci Susiawati; Elih Sutisna Yanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study reports the findings of an action research study on student responses to reading comprehension of narrative text using story mapping. The research questions are: (1) How are story mapping procedures implemented in learning reading comprehension of narrative text? (2) What are students' responses to these activities? The research was conducted to determine students' responses to reading comprehension of narrative text using story mapping. This study aims to determine students' responses to learning to read narrative texts in a reading comprehension program through story maps. The participants of this study were five high school students who were randomly selected to be interviewed. This research was conducted in a junior high school in West Java, Indonesia. Observation, interviews, and documentation were used to collect data in this study. Data analysis using theory (Braun & Clark 2006). The findings report that the story mapping technique can encourage students' interest in making it easier to understand the text and motivate students to read. However, due to limited time and recording equipment, this study still has its limitations.